Adherence to a healthy lifestyle in Russia according to the ESSE-RF study: is there a COVID-19 trace? - О. M. Drapkina; M. B. Kotova; S. A. Maksimov; S. A. Shalnova; Yu. A. Balanova; A. E. Imaeva; V. A. Kutsenko; G. A. Muromtseva; N. S. Karamnova; S. E. Evstifeeva; A. V. Kapustina; O. A. Litinskaya; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To assess adherence to a healthy lifestyle depending on the individual and socio-economic characteristics of the Russian population (according to the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study), followed by a comparative analysis with ESSE-RF2 (2017).Material and methods. The analysis was carried out based on research data from ESSE-RF2 in 2017 and ESSE-RF3 in 2020-2022. The healthy lifestyle adherence index included following parameters: no smoking; sufficient consumption of vegetables and fruits; physical activity; no excessive salt intake and alcohol abuse. Three following categories of adherence to a healthy lifestyle were analyzed: high, satisfactory, low. From individual variables, individual socio-economic characteristics with the highest evidence level of influence on healthy lifestyle were taken.Results. In the ESSE-RF3 sample, 47,2% of respondents had low adherence to a healthy lifestyle, 37,2% — satisfactory, and 15,6% — high. Women are more committed to healthy behavior compared to the male population — 19,6 vs 11,1% (p<0,001). The lowest adherence to a healthy lifestyle was found among men with low incomes who do not have higher education and is typical for younger people. Analysis of changes from 2017 to 2020-2022 revealed that adherence to a healthy lifestyle among the population decreased mainly due to a decrease in the proportion of people with high adherence.Conclusion. The study made it possible to characterize the current level of healthy lifestyle among the population and demonstrated the most promising strategies aimed at improving adherence to a healthy lifestyle among the Russian population.